Implementation of Problem-based Learning Model to Enhance Students Learning Outcomes in Buffer Solutions Topic - Lousia Vionalisa Letlora; Murtihapsari - Murtihapsari; Christiana Niken Larasati; Apriani Sulu Parubak; Achmad Rante Suparman; Putri Surbakti Sarera; Thelma - Aluman; Radite - Yogaswara (Jurnal Tadris Kimiya, 2021)
This research aims to determine the improvement of the process and learning outcomes of the buffer solutions topic by applying the Problem-based Learning (PBL) model. This research is based on Classroom Action Research (CAR) takes place in two cycles, with several stages including planning, implementing, observing, and reflecting. Our present study used 17 students of natural science 11th grade SMA Advent Manokwari. The data was obtained from teachers and students. The data collection method used cognitive learning outcomes and observation. The data analysis uses descriptive analytic techniques. Our findings showed that the application of the PBL model can improve the quality of the learning process on the buffer solutions topic; the application of the Problem-based Learning (PBL) learning model has increased from cycle I with an average grade of 65.36 and a percentage of passing grades of 41% and cycle II with an average grade of 83.66 and a percentage of passing grades of 88%.